A mother like mine - Hewitt, Kate (Hewitt, Kate. Hartley-by-the-Sea novel., 2017)
"Welcome to England's beautiful Lake District, where a reluctant reunion forges a new bond between a daughter and her wayward mother.... Abby Rhodes is just starting to get her life on track. After her fiance's unexpected death, she returned with her young son to the small village where she grew up and threw herself into helping her ailing grandmother run the town's beach cafe. Then one evening, her mother, Laura, shows up in Hartley-by-the-Sea and announces her plan to stay. After twenty years away, she now wants to focus on the future--and has no intention, it seems, of revisiting the painful past. Laura Rhodes has made a lot of mistakes, and many of them concern her daughter. But as Abby gets little glimpses into her mother's life, she begins to realize there are depths to Laura she never knew. Slowly, Abby and Laura start making tentative steps toward each other, only to have life become even more complicated when an unexpected tragedy arises. Together, the two women will discover truths both sad and surprising that draw them closer to a new understanding of what it means to truly forgive someone you love"--